2020
DOI: 10.17582/journal.pjz/20170317130336
|View full text |Cite
|
Sign up to set email alerts
|

Damages Done by Black Bear (Ursus thibetanus) in Moji Game Reserve and its Surroundings, Leepa Valley, Azad Jammu and Kashmir (Pakistan)

Abstract: Photoperiod and shelter have direct or indirect effects on phenotypic traits expression in different fish species. The present study was, therefore, intended to explore whether these light and shelter could influence some phenotypic traits of African catfish larvae under laboratory condition. Newly hatched larvae were stocked in plastic aquaria (10L) at a rate of 5 individuals/L and reared for one month under four treatments such as 24h light (24L), 24 h dark (24D), 12h light and 12h dark with PVC (12DL_PVC), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 69 publications
1
20
0
Order By: Relevance
“…Previous studies reported high intensities of human black bears con icts in Pakistan (Ali et al 2017; Kazmi et al 2019;Waseem et al 2020;Zahoor et al 2021c;Zahoor et al 2021d), however, there is no study available on activity pattern of black bears. In Taiwan, it was reported that in oak poor season, bears activity decreased and vice versa (Hwang and Garshelis 2007).…”
Section: Introductionmentioning
confidence: 98%
See 4 more Smart Citations
“…Previous studies reported high intensities of human black bears con icts in Pakistan (Ali et al 2017; Kazmi et al 2019;Waseem et al 2020;Zahoor et al 2021c;Zahoor et al 2021d), however, there is no study available on activity pattern of black bears. In Taiwan, it was reported that in oak poor season, bears activity decreased and vice versa (Hwang and Garshelis 2007).…”
Section: Introductionmentioning
confidence: 98%
“…Black bears are often involved in livestock depredation and crop raiding, therefore are usually killed in retaliation by the local people (Charoo et al 2011; Jamtsho and Wangchuk 2016). The con ict starts from late spring that gradually intensi es at the end of autumn and attains its peak when maize (Zea mays) crop, one of its favorite food, is at ripening stage (Ali et al 2017, Kazmi et al 2019Zahoor et al 2021c; Zahoor et al 2021d). People using maize grains as a staple food source and other vegetal parts as fodder for livestock (Zahoor et al, 2021c) come in con ict with black bear during crop raiding.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations